Is there a benefit of lymphadenectomy for overall and recurrence-free survival in type I FIGO IB G1-2 endometrial carcinoma? A retrospective population-based cohort analysis - Papathemelis, Thomas; Hassas, Dunja; Gerken, Michael; Klinkhammer-Schalke, Monika; Scharl, Anton; Lux, Michael P.; Beckmann, Matthias; Scharl, Sophia (Journal of Cancer Research and Clinical Oncology, 2018)
The recommended therapy for type I FIGO IB endometrial cancer (EC) is hysterectomy and adnexectomy, but the therapeutic benefits of additional pelvic and paraaortic lymph node dissection (LND) are still under discussion. In this study, we retrospectively evaluated overall survival (OAS) and recurrence-free survival (RFS) among patients with type I FIGO IB EC who did undergo systematic or elective lymphadenectomy or none at all.We selected 299 individuals from the database of the German Tumor Centre Regensburg who were diagnosed between 1998 and 2015 with endometrial adenocarcinoma of the uterus type I FIGO IB. We applied multivariable Cox regression to the selected patient data and estimated hazard ratios for OAS and RFS against the performed intervention. Further, we carried out risk adjustments with respect to clinicopathological parameters, and performed model selection using conditional stepwise forward selection.We observed significant benefits of LND in the unadjusted survival analysis; however, we did not confirm this effect in multivariable regression analysis upon risk adjustment. In this case, hazard ratio (HR) for OAS in patients without LND versus patients with LND is reduced to 1.214 (95% CI 0.771-1.911; p = 0.402), HR for RFS is 1.059 (95% CI 0.689-1.626; p = 0.795). Similarly, we were also able to eliminate the statistical benefit of systematic versus elective LND by risk adjustment.In contrast to previous observations in high-grade EC, our study provides compelling evidence that LND, in particular systematic lymphadenectomy, is not beneficial for patients with type I FIGO IB EC in terms of long-term OAS and RFS.
EVALuna2:92113